THE LINK BETWEEN FOREIGN DIRECT INVESTMENTS AND ECONOMIC GROWTH: EMPIRICAL STUDY FROM SELECTED EU COUNTRIES - Węgrzyn, Paweł (Torun International Studies, 2025)
Purpose: The main focus of this research is the relationship between Foreign Direct Investments (FDI) and economic growth in 22 member countries of both the European Union (EU) and the Organization for Economic Co-operation and Development (OECD). The study aims to ascertain if FDI significantly impacts economic growth within these countries and to determine the extent of differentiation in this impact across different countries. Methodology/approach: Utilising the Granger causality test, FDI's influence on GDP in the Granger sense was identified in a substantial portion of the investigated countries. This relationship's depth and direction were further delineated using multiple regression models with distributed lags (DL). Additionally, each country's data was individually assessed to spotlight variations in FDI's influence on GDP. Integral macroeconomic control variables—such as inflation, the unemployment rate, and the public debt to GDP ratio—were included, ensuring a more holistic understanding of GDP determinants. Findings: Results indicated that approximately half of the countries display a statistically significant positive impact of FDI on GDP. Notably, no country exhibited a negative, significant relationship. An ensuing cluster analysis conveyed that not the least developed countries but those marked by advanced development and relatively low indebtedness showcased pronounced FDI impacts on GDP. In my research, Poland was identified as a unique case, which, despite its relatively lower GDP per capita compared to other countries, displays a significant influence of FDI on economic growth. Originality/value: This research delivers empirical evidence highlighting the instrumental role of FDI in amplifying GDP from the recipient country's perspective, reinforcing its essentiality in shaping economic trajectories by particular countries.